Temporal trends and predictors of gestational exposure to organophosphate ester flame retardants and plasticizers - P.A. Bommarito; A. Friedman; B.M. Welch; D.E. Cantonwine; M. Ospina; A.M. Calafat; J.D. Meeker; T.F. McElrath; K.K. Ferguson (Environment International, 2023)
Background: Organophosphate esters (OPEs), used as flame retardants and plasticizers, are chemicals of concern for maternal and infant health. Prior studies examining temporal trends and predictors of OPE exposure are primarily limited by small sample sizes. Objectives: Characterize temporal trends and predictors of OPE exposure biomarkers. Methods: We determined urinary concentrations of eight biomarkers of OPE exposure at three timepoints during pregnancy for participants in the LIFECODES Fetal Growth Study (n = 900), a nested case-cohort recruited between 2007 and 2018. We examined biomarker concentrations, their variability during pregnancy, and temporal trends over the study period. In addition, we identified sociodemographic and pregnancy characteristics associated with biomarker concentrations. Analyses were conducted using both the within-subject pregnancy geometric means and biomarker concentrations measured at individual study visits. Results: Five OPE biomarkers were detected in at least 60% of the study participants. Biomarkers were not strongly correlated with one another and intraclass correlation coefficients, measuring within-subject variability during pregnancy, ranged from 0.27 to 0.51. Biomarkers exhibited varying temporal trends across study years. For example, bis(1-chloro-2-propyl) phosphate (BCIPP) increased monotonically, whereas bis(1,3-dichloro-2-propyl) phosphate (BDCIPP) and diphenyl phosphate (DPHP), displayed non-monotonic trends with concentrations that peaked between 2011 and 2014. We observed associations between sociodemographic characteristics and OPE biomarkers. In general, concentrations of most OPE biomarkers were higher among participants from racial and ethnic minority populations, participants who were younger, had higher pre-pregnancy body mass index (BMI), and less than a college degree. We observed consistent results using either averaged or visit-specific biomarker concentrations. Significance: We observed widespread exposure to several OPEs and OPE biomarkers displayed varying temporal trends in pregnant people from 2007 to 2018. Concentrations of most OPE biomarkers varied according to sociodemographic factors, suggesting higher burdens of exposure among participants with higher pre-pregnancy BMI, those belonging to racial and ethnic minority populations, and lower educational attainment.